Theoretical investigation of lattice-matched III-N-V/Si double-junction solar cells. (24th November 2022) - Zhang, Xiaobin; Liu, Liming; Chi, Feng; Wang, Ke; Lin, Kaiwen; Wang, Yuehui
Abstract: The lattice-matched III-N-V/Si double-junction (DJ) solar cells are designed with GaNAsP and GaInNP top cells, respectively. Under AM1.5G condition, the efficiencies of III-N-V/Si DJ cells are calculated with variable electron lifetime ( τe ) and electron surface recombination velocity ( Se ) in top cell. When Se is 100 cm s −1 and τe rises from 1 to 1000 ns, the optimal efficiency of GaNAsP/Si cell increases from 31.12% to 36.13% due to the increasing short-circuit current and open-circuit voltage. With τe of 100 ns, the optimal efficiency keeps at a high value of ∼35% when Se changes from 10 to 1000 cm s −1, but drops obviously with Se of 10 000 cm s −1 . In comparison, the optimal efficiency of GaNAsP/Si cell is less sensitive to Se than to τe . With fixed Se of 100 cm s −1, GaNAsP/Si cell shifts the optimal top-cell bandgap from 1.716 to 1.787 eV when raising τe from 1 to 1000 ns. However, the effect of Se on optimal top-cell bandgap is negligible. For III-N-V/Si cell with 100 ns τe and 100 cm s −1 Se, an optimal efficiency is obtained as ∼35.1%, which would be closer to the experimental limit owing to the expectable values of τe and Se . Furthermore, the optimal efficiency of GaNAsP/Si cell drops slightly when thinning Si substrate from 300 to 150 μ m, but has a maximum of 35.95% with substrate doping of 1 × 10 16 cm −3 when the doping concentration varies from 1 × 10 15 to 1 × 10 18 cm −3 . The results and discussion in this work may act as a guidance for studying III-N-V/Si DJ cell.